Effectiveness of a cognitive-behavioral intervention to increase functional coping strategies and positive mental health in Mexican university students - Toribio Pérez, Lorena; Andrade Palos, Patricia (Pensando Psicología, 2025)
The objective was to evaluate the effectiveness of an online intervention program to increase the use of functional coping strategies and positive mental health in Mexican university students, based on cognitive-behavioral therapy. The sample consisted of 73 participants aged 18 to 30 years (M=21.7, SD=3.6), 64.4% were women and 35.6% were men. 36 participants were assigned to the experimental group and 37 to the control group. The Coping Scale and the Mental Health Continuum, short version (Mental Health Continuum Short Form) were applied. The five-session intervention program was applied to the experimental group; the control group received no intervention. A post-intervention evaluation was performed. Significant differences were found post-intervention in the experimental group in functional coping (t=-1.110, p=0.001), positive thinking and search for solutions (t=-2.545, p=0.015), search for support in the peer group (t=-2.945 p=0.006) and religion (t=-2.667, p=0.012), likewise significant differences were observed in positive mental health (t=-2.995, p=.005), emotional well-being (t=-3.097, p=0.004), psychological well-being (t=-2.830, p=0.029) and social well-being (t=-2.135, p=0.040). Regarding the control group, there were no significant differences in functional, dysfunctional coping and positive mental health. The program intervention proved to be effective in increasing the use of functional coping strategies and positive mental health in the experimental group. It is recommended to review and apply the program in other samples to verify its effectiveness and validity.